2001
DOI: 10.1046/j.1471-4159.2001.00212.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glutathione depletion by 2‐cyclohexen‐1‐one on excitatory amino acids‐induced enhancement of activator protein‐1 DNA binding in murine hippocampus

Abstract: We have investigated the role of glutathione in mechanisms associated with excitatory amino acid signaling to the nuclear transcription factor activator protein-1 (AP1) in the brain using mice depleted of endogenous glutathione by prior treatment with 2-cyclohexen-1-one (CHX). In the hippocampus of animals treated with CHX 2 h before, a signi®cant increase was seen in enhancement of AP1 DNA binding when determined 2 h after the injection of kainic acid (KA) at low doses. The sensitization to KA was not seen in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Melatonin also prevented the neurotoxic effects of ROS generated by KA receptor activation through an increase in intracellular GSH (Floreani et al, 1997). Therefore, GSH may protect neuronal cells against KA neurotoxicity through a mechanism associated with ROS scavenging (Kim et al, 2000a; Kitayama et al, 1999; Ogita et al, 2001; Yoneda et al, 2001). …”
Section: Seizure-induced Oxidative Damagementioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin also prevented the neurotoxic effects of ROS generated by KA receptor activation through an increase in intracellular GSH (Floreani et al, 1997). Therefore, GSH may protect neuronal cells against KA neurotoxicity through a mechanism associated with ROS scavenging (Kim et al, 2000a; Kitayama et al, 1999; Ogita et al, 2001; Yoneda et al, 2001). …”
Section: Seizure-induced Oxidative Damagementioning
confidence: 99%
“…A previous study showed that prolonged GSH depletion may lead to sensitization of the KA receptor to potentiate AP-1 DNA-binding activity in the murine hippocampus (Kitayama et al, 1999; Ogita et al, 2001; Yoneda et al, 2001), suggesting that endogenous GSH may be partly involved in the underlying molecular mechanisms of transcription control by KA (Kitayama et al, 1999; Ogita et al, 2001; Yoneda et al, 2001). Changes in AP-1 DNA-binding activity were qualitatively similar to those observed with NF-kB in the adult rat brain (Rong and Baudry, 1996).…”
Section: Seizure-induced Oxidative Damagementioning
confidence: 99%
“…Moreover, PDYN promoter has an AP-1 binding site. Taking into account that AP-1 might be central in transcriptional cascades that follow an induced seizure in epilepsy experimental models [16] and that dynorphins have an important role in neuronal homeostasis regulating the opening of K+ channels [4], it can be suggested that functional variants in PDYN could be plausibly involved in TLE epileptogenesis. Furthermore, dynorphins are extensively expressed in dentate gyrus' granular cells [17].…”
Section: Discussionmentioning
confidence: 99%